Critical care after major surgery: a systematic review of risk factors for unplanned admission. (5th January 2020) - Onwochei, D. N.; Fabes, J.; Walker, D.; Kumar, G.; Moonesinghe, S. R.
Summary: Critical care admission may be necessary for surgical patients requiring organ support or invasive monitoring in the peri‐operative period. Unplanned critical care admission poses a potential risk to patients and pressure on services. Existing guidelines base admission criteria on predicted risk of 30‐day mortality; however, this may not provide the best predictor of which patients would benefit from this service, and how unplanned admission might be avoided. A systematic review of MEDLINE, Embase, CINAHL, Web of Science, the Cochrane database and the grey literature identified 44 studies assessing risk factors for unplanned critical care admission in adult populations undergoing non‐cardiac, non‐thoracic and non‐neurological surgery. Comparative, quantitative analysis of the admission criteria was not feasible due to heterogeneity in study design. Age, anaemia, ASA physical status, body mass index, comorbidity burden, emergency surgery, high‐risk surgery, male sex, obstructive sleep apnoea, increased blood loss and operative duration were all independent risk factors for unplanned critical care admission. Age, body mass index, comorbidity extent and emergency surgery were the most common independent risk factors identified in the USA, UK, Asia and Australia. These risk factors could be used in the development of a risk tool or decision tree for determining which patients might benefit from planned critical care admission. Future work should involve testing the sensitivity and specificity of these measures, either alone or in combination, to guide planned critical care admission, reduce patient deterioration and unplanned admissions.